2018
DOI: 10.1161/strokeaha.118.021819
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Insights From Vessel Wall Imaging of Unruptured Intracranial Aneurysms

Abstract: Background and Purpose— The clinical significance of vessel wall imaging (VWI) remains unclear in patients with unruptured intracranial aneurysms. This study was performed to investigate the correlations between aneurysm wall imaging findings and histopathologic aneurysm wall architectures. Methods— A total of 9 aneurysms was evaluated by VWI and subsequently characterized with histopathology. We used VWI to visualize the aneurysm wall and determine if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(77 citation statements)
references
References 12 publications
2
72
1
Order By: Relevance
“…Recent advance in magnetic resonance vessel wall imaging (MR-VWI) has shown association between wall enhancement and aneurysm rupture (20). Further histopathological analyses revealed that wall enhancement was associated with wall thickening with atherosclerotic change (21,22). Our study suggested that increased lipid infiltration was associated with rupture, which was in line with these new findings from vessel wall imaging.…”
Section: Discussionsupporting
confidence: 86%
“…Recent advance in magnetic resonance vessel wall imaging (MR-VWI) has shown association between wall enhancement and aneurysm rupture (20). Further histopathological analyses revealed that wall enhancement was associated with wall thickening with atherosclerotic change (21,22). Our study suggested that increased lipid infiltration was associated with rupture, which was in line with these new findings from vessel wall imaging.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, the pattern of AWE is significantly associated with the morphological changes observed in IAs, such as aneurysmal sac expansion or daughter sac formation [31]. It remains controversial if AWE could serve as potential imaging modality capable of identifying unstable IAs [32,33], as 20-40% of stable unruptured IAs may also demonstrate the AWE [19,31,34]. In our study, AWE did not have a high PPV for MBs associated with SH, but lack of AWE had a high NPV.…”
Section: Discussioncontrasting
confidence: 47%
“…27 Vessel wall imaging in humans has shown that aneurysm wall enhancement corresponds histopathologically to wall thickening, wall atherosclerosis, neovascularization, and macrophage infiltration. 36 domes were resected for histological analysis. 20 Increased wall thickness and macrophage infiltration were correlated to both vessel wall enhancement and rupture.…”
Section: Discussionmentioning
confidence: 99%